Пошаговое объяснение:
z=1+4i
z=1-4i
Пусть z = x
(x-(1+4i))(x-(1-4i))=0
(x-1-4i)(x-1+4i)=0
x*x-1*x+4i*x-1*x+1-4i-4ix+4i-4i*4i=0
x²-x-x-4i+4i+16+1=0
x²-2x+17=0
Обратно:
z²-2z+17=0
x²–2x+17=0
z=1+4I
z=1–4I
z=x
(x–(1+4i)(1-4i))=0
(x–1–4i)
(x–1–4i)(x+1+4i)=0
x•x–1•x+4i•x–1•x+1–4i–4ix+4i–4i•4i=0
x²–x–x–4i+4i+16+1=0
Пошаговое объяснение:
z=1+4i
z=1-4i
Пусть z = x
(x-(1+4i))(x-(1-4i))=0
(x-1-4i)(x-1+4i)=0
x*x-1*x+4i*x-1*x+1-4i-4ix+4i-4i*4i=0
x²-x-x-4i+4i+16+1=0
x²-2x+17=0
Обратно:
z²-2z+17=0
x²–2x+17=0
Пошаговое объяснение:z=1+4I
z=1–4I
z=x
(x–(1+4i)(1-4i))=0
(x–1–4i)
(x–1–4i)(x+1+4i)=0
x•x–1•x+4i•x–1•x+1–4i–4ix+4i–4i•4i=0
x²–x–x–4i+4i+16+1=0
x²–2x+17=0